Ethical events in nursing: daily activities of nurse managers and nursing ethics committee members Ocurrencias éticas de enfermería: el cotidiano de los enfermeros gerentes y miembros de la comisión de ética de enfermería Ocorrências éticas de enfermagem: cotidiano de enfermeiros gerentes e membros da comissão de ética de enfermagem - Genival Fernandes de Freitas (Revista Latino-Americana de Enfermagem, 2006)
This study aimed to understand the meaning of nurses' actions related to ethical occurrences involving nursing professionals. Data were collected through interviews with nurse managers and members of a Nursing Ethics Committee who experienced the phenomenon. Data were analyzed in the framework of social phenomenology. The nurses' experiences gave rise to the following categories of meaning, as these professionals seek: the humanization of nursing care; continuous improvement of the care process; professional credibility; patients' satisfaction; demystification of the fear of punishment; partnership in the educational process; respect for ethical secrecy and expectation related to the event being forwarded to the Nursing Ethics Committee. The social typification was described at the end. Nurses' actions in cases of ethical events attract the interest of nursing professionals, who want to ensure a risk or damage-free care and to promote the valuation of these professionals. El objetivo de este estudio fue comprender el significado de las ocurrencias éticas involucrando a profesionales de enfermería. Los datos fueron obtenidos por medio de entrevistas con enfermeros gerentes y enfermeros miembros de la Comisión de Ética de Enfermería que pasaron por el fenómeno. Los datos fueron analizados según la perspectiva de la fenomenología social. Las experiencias de los enfermeros posibilitaron desvelar las siguientes categorías concretas del significado del vivido, pues ellos buscan: la humanización de la atención; la mejoría continua del proceso de cuidar, la credibilidad profesional; la satisfacción de la clientela; las demistificación del miedo de la punición, el compartir en el proceso educativo; el respeto al sigilo ético y la expectativa relacionada al posible envío de la ocurrencia a la Comisión de Ética. La tipificación fue descrita al final. Las acciones de los enfermeros en las ocurrencias éticas despiertan interés de los profesionales de enfermería, que desean garantizar una atención libre de riesgos/daños y promover la valorización de esos profesionales. O objetivo deste estudo foi compreender o significado das ações dos enfermeiros frente às ocorrências éticas envolvendo os profissionais de enfermagem. Os dados foram obtidos por meio de entrevista com enfermeiros gerentes e enfermeiros membros da Comissão de Ética de Enfermagem que vivenciaram o fenômeno. Os dados foram analisados segundo o referencial da fenomenologia sociológica. As experiências dos enfermeiros permitiram desvelar as seguintes categorias concretas de significado vivido, pois eles buscam: a humanização da assistência, a melhoria contínua do processo de cuidar, a credibilidade profissional, a satisfação da clientela, a desmistificação do medo da punição, a parceria no processo educativo, o respeito ao sigilo ético e a expectativa em relação ao encaminhamento da ocorrência à Comissão de Ética. A tipificação foi descrita ao final. As ações dos enfermeiros nas ocorrências éticas despertam o interesse dos profissionais de enfermagem, que querem assegurar uma assistência isenta de riscos ou danos e promover a valorização desses profissionais.